AKIBAT HUKUM PERUSAHAAN YANG MELAKUKAN PHK TERHADAP PEKERJA DENGAN ALASAN EFISIENSI SESUAI PASAL 164 AYAT (3) UU NO 13 TAHUN 2003 (STUDI KASUS PT. RAFI KAMAJAYA ABADI DI KABUPATEN MELAWI ) - NIM. A1012161180, KRISTIAN MAHARSON HOLY SAPUTRA (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACTTermination of employment refers to the end of the employment relationship between employers and employees. Termination of employment also has a negative connotation because it is often the employer who terminates the employment agreement. In fact, employment agreements are built together when both parties need each other. Employers need workers to build their business and workers also need wages for what they have done. In particular, for companies, terminating employment is a detrimental action in which the company has trained and educated workers at great expense so that these workers have competence in their fields of work. In the industrial sector, it is not uncommon to find companies that use the word